The Symbols of Anxiety in Rumaan Alam’s “Leave The World Behind” - Ridho Pratama Satria; Wilma Prafitri; Fatimah Muhajir (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2026)
This research examines the meanings of the symbols appearing in Rumaan Alam's novel "Leave The World Behind." The discussion for the meaning of these symbols utilize the New Criticism theory. This study found two important symbols from the story: the house and the animal (deer and flamingo). The house represents the calm and well-prepared personality of the homeowner. The animals represent the mode or the passage of transportation. These symbols emerge to explain the issue of anxiety inherent in humans. The animals represent the full meaning of anxiety. When anxiety arises, humans tend to flee to protect themselves. The house represents the need to remain calm and prepared to face the anxiety that arises.